Indicators of Sustainable Production in Chemical Enterprises - Vávra, Jan; Vrbická, Tereza (AMCA, spol. s r.o., 2023)
The growing pressure of the public on the sustainable behavior of companies is causing changes in the product portfolio as well as changes in production processes in all industries. The ongoing digitization of business processes facilitates production, helps monitor production processes, and ensures high quality and competitiveness. Chemical production companies are also adapting to the transformation of the industry and, even concerning the rising prices of resources, they are trying to produce sustainably. The sustainability of production and products needs to be monitored through appropriate indicators. Their use and utilization were mapped by qualitative research in a selected chemical company. The dimensions of sustainability were identified according to the triple-bottom-line concept and the key indicators of production sustainability evaluation were verified in them.
Indikátory udržitelné výroby v chemických podnicích
Keywords: performance indicators; sustainable production; digitization; ukazatele výkonnosti; udržitelná výroba; digitalizace